Kewajiban Notaris dalam Pembuatan Akta Guna Mewujudkan Notaris yang Berintegritas di Era Globalisasi - Agustin Rifiana; Yetniwati Yetniwati; Diana Amir (Universitas Batanghari Jambi, 2022)
The purpose of this study was to know and analyze a notary setting that grits are reviewed in terms of UUJN and the prospect of notary who the grits are faced with the era of globalization. This research uses normative method. The approach used is statute approach and conceptual approach. The results of this study are carry out legal tasks and positions in conducting legal actions such as making authentic deed and privately made deed must with UUJN, code of ethics and other regulations regarding the task of the notary as a public official. The most important thing for a notary is to cary out his duties properly in accordance with UUJN, and has not carried out the forbidden act listed in UUJN and other regulations regarding his duties. The development in the globalization of a notary still has to carry out their jobs according to the profession. The era of notary publicization that is gritted also has to have a wide insight into, not only makes deeds but must be intelligent in responding to clients in making deeds, having high moralitys, and not prioritized personal interests, notary jobs should be more careful.